Child growth and armed conflict - Noël Cameron (Taylor & Francis Group, 2023)
Background During armed conflict, the non-combative population, and particularly children, are susceptible to the effects of conflict from a variety of perspectives; psychological stress, loss of food and resources, loss of accommodation, occupation, income, death of family members, etc. The Lancet recently published a special issue entitled 'Maternal and child health and armed conflict' concluding that the ways in which health can be affected by conflict are protean but systematic evidence is sparse, whatever evidence exists is localised and of low to moderate quality, and that data on adolescents are sparse to non-existent. Whilst this may be true of the challenging environments of conflicts in developing countries, historically recent conflicts in Europe provide an alternative viewpoint that is frequently aired in the Auxological literature but is virtually unknown and/or unrecognised in health settings. Methods The current paper summarises three previously published studies based on repeated cross-sectional child growth surveys in London, Oslo, and Stuttgart covering the years of the Second World War. Taken together these studies provide extensive evidence of the response of children to armed conflict in the context of secular tends in growth of children living in industrialised nations during the twentieth century. Conclusions The conclusions to all three studies may be summarised, with regard to children in industrialised nations, as: (1) armed conflict adversely affects human growth and health, (2) armed conflict affects all age groups but adolescents more so, (3) all age groups recover from poor growth as conditions improve in relation to post-war health and welfare programmes, (4) pre-war differences in size between SES groups diminish during post-war recovery when accompanied by nutritional, welfare and reconstruction programmes.